Aktivitas Terbang Sebelum Migrasi dan Identifikasi Polen Pada Madu Apis dorsata di Kampar, Riau: Flight Activity Before Migration and Pollen Identification from Honey of Apis dorsata in Kampar, Riau - Dyahastuti, Meis; Raffiudin, Rika; Widjaja, Mochammad Chandra; Afriani, Nita; Listyowati, Sri (Jurnal Sumberdaya Hayati, 2022)
The scarcity of nectar and pollen resources are the most problems encountered by the giant forest honey bee Apis dorsata in many places in Indonesia, including those in Kampar, Riau. Due to the environment condition, many bees abscond and migrate to find blooming regions. Thus, we aimed to analyze flight activity of the returning A. dorsata with- and without pollen as well as the pollen diversity in the honey. Flight activities were observed by counting the number of returning bees carrying with and without pollen in 3 days. Pollen from A. dorsata honey was collected and extracted and were acetolyzed for pollen identification. We observed an unusual behaviour that is, the peak of flight activities occurred at 11-12 am. These honey bee time flights are not  typical of foraging time activities. Our puzzled revealed that on the day after the last observation, we found that the bees abscond  and leaving an empty nest. Thus, we concluded that the noon flight activities were the sign for the flight preparation for migration. In the honey of A. dorsata, we found the most source pollen of A. dorsata is a tree which are Pentace sp. (64%), Eucalyptus alba (22.9%) and E. guineensis (4%).